Evaluation Of Dna Damage By Comet And Mtt-Assay In Liver Treated With Polygonum Bistorta And Tannic Acid - DEEPAK KUMAR MITTAL,; DEEPMALA JOSHI, (International Journal of Pharma and Bio Sciences, 2012)
Herbal preparations have been recommended in alternative systems of medicine for the treatment of hepatic disorders. Among the various studies involved in toxic, effect of CCl4 (1.5 ml/kg, i.p.) is oxidative damage through free radical generation. Drug-induced hepatotoxicity is still a significant unresolved clinical problem as liver is the most common site of damage. Polygonum Bistorta (PB) is powerful astringent, demulcent, diuretic, febrifuge, laxative, strongly styptic and rich in tannins. No systematic study has been done on protective efficacy of (PB) and Tannic acid (TA) to treat hepatic damage. The goal of work is to evaluate the efficacy of root extract of PB (100 mg/kg) and TA (25 mg/kg, p.o.) against CCl4 induced damage in liver. The activities of comet assay and MTT assay significantly recovered the damage towards normal and also reversed the histopathological alterations in liver. Thus, it may be concluded that PB and TA can be used to reduce the hepatic damage. Thus, it may be concluded that TA more effective towards control.